2010
DOI: 10.1111/j.1463-1326.2010.01265.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of metabolically generated reactive oxygen species for lipotoxicity in pancreatic β‐cells

Abstract: Chronically elevated concentrations of non-esterified fatty acids (NEFAs) in type 2 diabetes may be involved in β-cell dysfunction and apoptosis. It has been shown that long-chain saturated NEFAs exhibit a strong cytotoxic effect upon insulin-producing cells, while short-chain as well as unsaturated NEFAs are well tolerated. Moreover, long-chain unsaturated NEFAs counteract the toxicity of palmitic acid. Reactive oxygen species (ROS) formation and gene expression analyses together with viability assays in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
141
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(149 citation statements)
references
References 82 publications
(151 reference statements)
2
141
0
6
Order By: Relevance
“…In any case, the mechanisms by which (gluco)lipotoxicity impacts the genes involved in β cell-β cell communication such as Cx36 are still largely obscure, but may involve enhanced peroxisomal fatty acid oxidation, production of ROS, and repression of cAMP-response elements (44,61).…”
Section: Figurementioning
confidence: 99%
“…In any case, the mechanisms by which (gluco)lipotoxicity impacts the genes involved in β cell-β cell communication such as Cx36 are still largely obscure, but may involve enhanced peroxisomal fatty acid oxidation, production of ROS, and repression of cAMP-response elements (44,61).…”
Section: Figurementioning
confidence: 99%
“…FA-induced beta cell apoptosis involves a variety of signalling mechanisms, including endoplasmic reticulum (ER) stress induction [4], mitochondrial dysfunction [5], activation of specific intracellular kinases such as the members of the mitogen-activated protein kinase (MAPK) family c-Jun N-terminal kinase (JNK) and p38 MAPK [6,7] and protein kinase C (PKC)δ [8], and peroxisome-generated reactive oxygen species (ROS) [7,9]. The tumour suppressor protein p53 is also implicated in FA-induced beta cell apoptosis [7,10], since both palmitate and oleate were shown to stimulate apoptosis of NIT-1 beta cells through p53 [7], and p53 inhibition was found to be involved in growth factor-dependent promotion of beta cell survival via Akt/protein kinase B [10].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that palmitate induces ROS generation in various cells such as skeletal muscle cells [13], THP-1 monocytes [12], pancreatic islet cells [38], and adipocytes [39] mainly through the activation of the NADPH (nicotinamide adenine dinucleotide phosphate) oxidase system [12]; they may also be formed as by-products of mitochondrial oxidative phosphorylation [37]. These ROS stimulate JNK activation [28] and induce mitochondrial dysfunction [15].…”
Section: Discussionmentioning
confidence: 99%